Application Of Picture Media In Project-Based Learning To Improve Student Discipline And Activeness In PPKN Learning - Rezkya Annisaa; Muh Sharim Haqqani; Nadrah (PT. Padang Tekno Corp, 2026)
This classroom action research aims to improve students’ understanding of norms and rules in everyday life through the use of picture-based learning media in Grade II UPT SD Negeri 74 Bontorita II during the 2025/2026 academic year. The study was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 22 students who were involved in learning activities using instructional pictures and number-pocket media to strengthen conceptual understanding. Data were collected through observation sheets, learning outcomes tests, and teacher reflections. The findings indicate a significant improvement in students’ learning outcomes and participation. Initial observations showed low understanding of norms and rules, reflected in students’ low discipline, responsibility, and adherence to class regulations. After the implementation of picture media in Cycle I, students’ average score increased from the pre-cycle score of 46.2% to 71.1%. In Cycle II, after using more varied and engaging visual media, students’ average score further improved to 79,36%, surpassing the minimum completeness criteria. The use of picture media was effective because it facilitated concrete understanding, increased motivation, and encouraged active engagement. The study concludes that picture-based media enhances students’ cognitive, affective, and behavioral competencies in learning. It is recommended that teachers integrate more innovative visual media to create meaningful, interactive, and enjoyable learning experiences in civics education and other subjects